2014
DOI: 10.1002/jso.23633
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maximal cytoreductive surgery plus regional heated intraperitoneal chemotherapy (HIPEC) on outcome of patients with peritoneal carcinomatosis of gastric origin: Results of the GYMSSA trial

Abstract: Maximal cytoreductive surgery combined with regional (HIPEC) and systemic chemotherapy in selected patients with gastric carcinomatosis and limited disease burden can achieve prolonged survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
132
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(149 citation statements)
references
References 41 publications
2
132
1
2
Order By: Relevance
“…Morbidity ranged from 3.8% to 49% for gastrectomy and from 14% to 21% for non-resection surgeries 43 . In the literature update, procedure-related morbidity in moderatequality noncurative studies ranged from 15.1% 44 to 88.8% 45 for gastrectomy and from 11.5% 46 to 21% 47 for non-resection surgeries.…”
Section: Key Evidence For Recommendationmentioning
confidence: 99%
“…Morbidity ranged from 3.8% to 49% for gastrectomy and from 14% to 21% for non-resection surgeries 43 . In the literature update, procedure-related morbidity in moderatequality noncurative studies ranged from 15.1% 44 to 88.8% 45 for gastrectomy and from 11.5% 46 to 21% 47 for non-resection surgeries.…”
Section: Key Evidence For Recommendationmentioning
confidence: 99%
“…Initially, this regionally focused approach was built on the concept of maximizing drug delivery to the sites of tumor and metastases while simultaneously elongating the therapeutic window by reducing systemic toxicity. Indeed, in a large phase III clinical trial in colorectal cancer spread to the peritoneum, HIPEC and CRS extended median survival from 12.6 to 22.3 months (P=0.032) (17). Likewise, small trials have indicated an association with prolonged survival when applying this technique to AGC with PC (23)(24)(25).…”
Section: Crs + Hipec Clinical Experience: Promising Resultsmentioning
confidence: 98%
“…The combined application of hyperthermia and chemotherapy has a significant synergistic effect (17)(18)(19)(20)(21). Hyperthermia can eliminate and inhibit the ability of some oncogenes in the target cells to control cellular uptake and drug excretion, hence decreasing drug excretion while increasing the cumulative drug concentration.…”
Section: Thermodynamic Effect Can Significantly Enhance the Response mentioning
confidence: 99%
“…The joint experience of 15 Western centres with crs and hipec for ptc of gastric origin, comprising150 patients, revealed an overall median survival duration of 9.2 months and a 5-year survival rate of 13% 56 58 . To summarize, the survival of patients with ptc of gastric origin after crs and hipec, although improved, remains considerably poor.…”
Section: Gastric Cancermentioning
confidence: 99%